Uso de nanocomposto como biofertilizante para o meloeiro - Santos, Thalita Gomes dos (2022)
In 2020, Brazil exceeded the production of 600 thousand tons and the 24 thousand hectares of melon planted area, however, the recent agreement with China gives the prospect that this production will double in the coming years. Technologies that make it possible to increase the production of cultivated plants without expanding the agricultural area have been developed with the aim of reducing environmental impacts in addition to exploiting the maximum productive capacity of agricultural species. In this context, biostimulants stand out, formulated products of biological origin that make it possible to increase the production of cultivated plants. Such an increase is due to the emerging properties of the constituents themselves, such as growth regulators or protective compounds, and not only as a consequence of the presence of essential nutrients for plants. Thus, the objective was to evaluate the development, production, gas exchange and photosynthesis of yellow melon in a protected environment under the effect of Arbolina®. The experiment was carried out in a greenhouse at Embrapa Agroindústria Tropical, in Fortaleza, CE. The experimental design used was completely randomized in a 5 x 2 factorial arrangement, with five concentrations of the biostimulant (0, 60, 120, 180 and 240 mg L-1) and two forms of application (via foliar and via irrigation water), with three replications and 4 plants per plot, totaling 30 experimental units and 120 plants. The following variables were evaluated: i) flowering - number of male and hermaphrodite flowers; ii) shoot - number of leaves, leaf area, fresh and dry mass of the leaf, length of primary branch, length and number of secondary branches, fresh and dry mass of branches; iii) fruit - fruit weight, length and width, skin thickness, pulp thickness, internal cavity, soluble solids and firmness; iv) gas exchange and photosynthesis – net photosynthetic rate, stomatal conductance, transpiration, instantaneous water use efficiency, instantaneous carboxylation efficiency and relative chlorophyll content. The number of melon leaves showed the maximum number of leaves at the estimated dose of 236 g/ha via foliar spraying, showing an increase of 10.01% in relation to the control. For the other variables analyzed, no significant differences were found between treatments. Thus, it can be concluded that the application of Arbolina® in melon plants did not change most of the parameters of development, production, gas exchange and photosynthesis for any of the forms of application, except the number of leaves, therefore not exerting a biostimulant effect. on melon culture.